Analysis of Groundwater Potential Using 1D Resistivity Method with Schlumberger Configuration to Address Water Scarcity in Meunasah Baro Village, Lhoknga District, Aceh Besar - Pocut Nurul Alam; Nurul Aflah; Izzan Nur Aslam; Ramzi Adriman; Agus Hari Pramana; Muchlis; Hendra Harisman (Universitas Syiah Kuala, 2026)
This community service activity focuses on identifying groundwater potential as an alternative solution to water scarcity in Meunasah Baro Village, Lhoknga District, Aceh Besar, Indonesia. The target beneficiaries were local residents who experience limited access to clean water, particularly during the dry season. The objective of this program was to provide scientific-based information on subsurface conditions to support sustainable water resource planning at the village level. A participatory and applied approach was implemented, involving local community members in site selection and field activities. The technical method used was a 1D resistivity geoelectrical survey with the Schlumberger configuration. Data were collected through field measurements and processed using inversion software to interpret subsurface lithology and groundwater characteristics. The results indicate that the subsurface layers are predominantly composed of silt and clay materials with low to moderate resistivity values. Although water-bearing layers were identified at depths of approximately 43 to 137.5 meters, the resistivity characteristics suggest that the groundwater is brackish. This condition is likely influenced by seawater intrusion due to the proximity of the study area to the coastline. No significant freshwater aquifer was identified.